Social Media, Identity, and Careful Culture: How Online Social Networks Limit Identity, Amplify Difference, and Diminish Social Cohesion. Issue 1 (2nd January 2023) - Balick, Aaron
ABSTRACT: Almost a decade after the publication of The Psychodynamics of Social Networking, this article develops its thesis further by addressing the socio-cultural frame in which social media is embedded. The ways in which identity is expressed online are deeply tied to powerful undercurrents of culture change and development. The architecture of social media serves to limit the expression of identity by fragmenting users into disparate online identity-based communities that enforce in-group norms, amplify differences between groups, and inhibit productive dialogue, empathy, and understanding. This creates a "careful culture" where certainty is amplified at the expense of ambivalence, uncertainty, and open exploration and dialogue. Real life examples from social media are utilized to illustrate the underlying dynamics that activate them.